Towards a Fleet of Robots for Orientation, Imaging, and Morphometric Analyses of Planktonic Foraminifera - Knappertsbusch, Michael; Eisenecker, Jean (Frontiers in Marine Science, 2022)
Morphometric shell measurements help to quantify evolutionary patterns of planktonic foraminifera (marine, calcite secreting protists). The study of shell variation of these organisms requires observations at stratigraphically high resolution, which entails morphometric measurements from thousands of specimens. Collection of such data is time-consming because of the need to orient specimens prior to imaging. In our agenda of studying menardiform globorotalids through time automated devices were developed to orientate and image specimens under incident light. The first of these robots - AMOR - was realized in 2009 and has proven advantageous for gathering morphometric data. AMOR consists of a motorized tilting stage enabling automatic orientation of specimens in a multicellular slide under a motorized binocular microscope. After collection of images from oriented specimens, shell parameters can be extracted and analyzed using separate digital imaging- and morphometric software. AMOR was strongly tuned to Globorotalia menardii, a species with a quasi-symmetric biconvex geometry in keel view and often with a non-circular periphery in aequatorial view. Improvemets of the software, that drives AMOR allow now orientation of spiro- and umbilico-convex profiles, and circular forms in aequatorial view such as in phylogenetically related species like G. miocenica and G. multicamerata. The improved program AMOR v. 3.28 was further increased for more flexibility using a scripting language for automated control of the Windows graphical user interface. This approach allows for case-by-case combination of fix functions in AMOR, that are required for orientation of a specimen, and which released us from re-programming sophisticated LabView code. Scripting of core-functions enables to develop „portfolios“ of adapted recipes for processing morphologies, that are beyond the menardiform morphogroup. To further expand on this concept a follow-up prototype – System AMOR 2 - was built and completed in March 2020. It integrates modified hardware, a newer digital camera, updated software (AMOR v. 4.2) with improved functions. The graphical user interface of AMOR v. 4.2 was extended by scriptable numeric input controls / numeric output indicators next to the buttons for activating core-functions. The present contribution describes the developments from old AMOR to the newer System AMOR 2.